First test field performance of highly efficient flat plate solar collectors with transparent insulation and low-cost overheating protection. (1st April 2022) - Kizildag, D.; Castro, J.; Kessentini, H.; Schillaci, E.; Rigola, J.
Abstract: The present work demonstrates prototypes of highly efficient flat plate solar thermal collectors prototypes based on transparent insulation materials (TIM) technology for efficiency improvement and an overheating protection system. The design and optimization of the collectors have been numerically carried out using a previously developed simulation tool based on an in-house software platform (NEST) capable of simulating all the entities constituting the system as a whole and using efficient coupling between the elements. Three design variants for the demonstration have been previously tested under laboratory conditions. These collectors are then mounted on the roof of a hospital building. Their performance is comparatively tested along with a conventional flat plate solar collector, under actual meteorological conditions and during long periods. The energy collected is about 2.5 and 1.4 times higher than standard collectors in winter and spring. Thus, due to the long-term exposure of the collectors, aspects such as reliability, durability, energy performance, and correct functioning of the protection system have been analyzed to improve the detected shortcomings for the future generations of the present design. Highlights: High efficiency, flat plate solar collectors based on TIM installed in demo site. Energy collected about 2.5 times higher respect standard collector in winter. Energy collected about 1.4 times higher respect standard collector in spring. Estimated costs about 30%–40% higher than a conventional flat plate collector. Overheating protection system must improve reliability to reach commercialization.